Intrathecal morphine reduces blood loss during idiopathic scoliosis surgery: retrospective study of 256 pediatric cases. Issue 3 (10th January 2013) - Lesniak, Aleksandra B.; Tremblay, Pierre; Dalens, Bernard J.; Aucoin, Maryse; Mercier, Pierre; Bosenberg, Adrian
Summary Background This retrospective cohort study was designed to assess the impact of intrathecal morphine compared with no intrathecal morphine on blood loss and on hemodynamic stability during surgery for pediatric idiopathic scoliosis correction. Methods A retrospective review was done of 256 anesthetic charts who underwent scoliosis surgery between January 1993 and February 2012 by the same orthopedic surgeon. 128 patients were operated on before 2003 without intrathecal morphine (NITM group) and 128 were treated later on with intrathecal morphine (ITM group).Primary endpoints were a 20% decrease in blood loss in the ITM group and hemodynamic stability. Results Both groups were similar for age, girl/boy ratio, weight and duration of surgery. Blood loss was significantly greater in the NITM group: 1793.1 ± 964.3 ml vs 655.8 ± 323.0 ml (P < 0.0001). Overall mean decrease in blood loss was 63.4% between the NITM group and the ITM group. A significantly (P < 0.0001) greater number of patients from the NITM group (122) received blood transfusions as compared to the ITM group (30). The volume of blood transfused per patient was significantly greater in the NITM group (701.4 ± 492.5 ml) than in the ITM group (293.7 ± 170.9 ml) (P < 0.0001). Heart rate was stable intra‐operatively in both groups. Variation in blood pressure >20% of baseline occurred more frequently in the NITM group (28.1%) than in the ITM group (14.8%) (P = 0.01). Conclusions These data demonstrate that intrathecal morphine in pediatric surgical scoliosis correction significantly decreases intra‐operative blood loss and transfusions and enhances blood pressure stability.